Pelatihan Peningkatan Branding Sekolah Di Amal Usaha Muhammadiyah Cerme Kabupaten Gresik - Moh Agung Surianto; Indro Kirono; Asep Saepulloh (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2023)
The high number of educational institutions in an area, especially in the Gresik Regency area, has implications for the level of competition in fighting over prospective new students. Every institution must be able to build school branding as the best place according to the educational needs of prospective new students and parents of students. The current service activity aims to build the branding of the Muhammadiyah Charity Business Cerme High School school under the auspices of the Basic and Middle Education Council (Dikdasmen) Muhammadiyah College, Cerme Branch, Gresik Regency. Community service activities are carried out in the form of offline training at the Muhammadiyah 8 Cerme High School location. The results of the Community Service show that there is an increase in the ability of school leaders in an effort to improve branding as an effort to increase public interest and positive perceptions, especially prospective students and parents of students.